![](http://hiphotos.baidu.com/zhidao/pic/item/fd039245d688d43f0602ef767e1ed21b0ff43b8e.jpg)
在△EIH中,由于DF∥IH,
∴
IH |
DF |
EI |
ED |
∵IH=AB,∴
AB |
DF |
EI |
ED |
从而,
AB |
DF |
AD |
DE |
EI |
ED |
AD |
ED |
EI−AD |
ED |
ED+AI |
ED |
AI |
ED |
在△OED与△OBH中,
∠DOE=∠BOH,∠OED=∠OHB,OD=OB,
∴△OED≌△OBH(AAS).
从而DE=BH=AI,
∴
AI |
ED |
由①,②得
AB |
DF |
AD |
DE |
AB |
DF |
AD |
DE |
IH |
DF |
EI |
ED |
AB |
DF |
EI |
ED |
AB |
DF |
AD |
DE |
EI |
ED |
AD |
ED |
EI−AD |
ED |
ED+AI |
ED |
AI |
ED |
AI |
ED |
AB |
DF |
AD |
DE |